ChemInform Abstract: State of the Art of Biodiesel Production Processes: A Review of the Heterogeneous Catalyst. Issue 9 (February 2016) - Ruhul, A. M.; Kalam, M. A.; Masjuki, H. H.; Fattah, I. M. Rizwanul; Reham, S. S.; Rashed, M. M.
Abstract: Review: 183 refs.